2010
DOI: 10.1089/acm.2009.0399
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Effect of Grounding on Delayed-Onset Muscle Soreness

Abstract: Objectives: The purpose of this pilot study was to determine whether there are markers that can be used to study the effects of grounding on delayed-onset muscle soreness (DOMS). Design and subjects: Eight (8) healthy subjects were exposed to an eccentric exercise that caused DOMS in gastrocnemius muscles of both legs. Four (4) subjects were grounded with electrode patches and patented conductive sheets connected to the earth. Four (4) control subjects were treated identically, except that the grounding system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 47 publications
(55 reference statements)
4
41
0
Order By: Relevance
“…19 A pilot study on delayed-onset muscle soreness demonstrated a remarkable reduction of inflammatory mediators, including a reduction in white blood cell count (lymphocytes, neutrophils, and eosinophils). 43 Attenuating inflammation and reducing blood viscosity will help physicians address primary and secondary prevention issues. Blood viscosity can be modified through a number of recognized primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…19 A pilot study on delayed-onset muscle soreness demonstrated a remarkable reduction of inflammatory mediators, including a reduction in white blood cell count (lymphocytes, neutrophils, and eosinophils). 43 Attenuating inflammation and reducing blood viscosity will help physicians address primary and secondary prevention issues. Blood viscosity can be modified through a number of recognized primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that contact with the Earth can affect regulation of immune response. 2,3 Earthing the human body during night-time sleep influences thyroid function: it increases concentrations of free T 4 and TSH and diminishes the level of free T 3 . The increase in basal metabolic rate accounts for the thermogenic effect of thyroid hormone that could be expressed in elevated utilization of free T 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were recently published and showed beneficial effects of grounding. [1][2][3][4] Dynamics of changes in measured parameters depends on several factors (e.g., disease and age of individuals, conditions of insulation of human body, the weather, body motion with longitudinal compression of skeleton, the period of grounding, the time of meals, and applied therapy). To eliminate the majority of these factors in experiments, the grounding has been done during night rest in a homogeneous group of people, however, in different time and weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous publications in the last decade claiming that health benefits can be realized by maintaining an electrical connection between the www.journalchiromed.com human body and ground [eg, [1][2][3][4][5][6][7][8][9][10][11] ]. This connection is referred to in the lay literature as grounding or earthing.…”
Section: Introductionmentioning
confidence: 99%